Phenomenological Study Of Students' Difficulties In Adjusting To University - Mira Dena Putri Panggabean; Ali Daud Hasibuan (Jurnal Ilmu Sosial Mamangan, 2024)
In everyday life, humans will be faced with various forms of adjustment, ranging from simple to complex, in which there is a pattern consisting of certain elements that can be seen clearly. For example, a child who longs for his mother's love is busy with other tasks to fulfill his life's needs. This research aims to determine the factors that cause students to have difficulty adjusting. With this research, we can find out what is the cause and effect of students at UIN North Sumatra class of BKPI-2 Stambuk 2020 in adapting. The method used in this research is descriptive qualitative. This research design uses a phenomenological study. Data collection techniques in this research are observation and interviews. The results of this research are that researchers can find out the factors that cause students to have difficulty adjusting based on emotional, intellectual, social and physical aspects. Physical aspects, a person's physique can influence a person's adaptation process. Several conditions, including hereditary factors, physical conditions, nervous system, glands and muscles, or disease, can affect the adaptation process. The conclusion of this research is that this factor becomes an obstacle for them which makes it difficult for them to accept and get along with new people. In this case, difficult to adapt does not mean it is impossible, but it takes quite a long time to be able to enter and blend into the new environment.